PELATIHAN SISTEM PEMESANAN KAMAR HOTEL BERBASIS DIGITAL DI TWINS HOTEL SYARIAH BANDUNG - Dwi Purnomo; Cahyadi; Heri Wiranto; Hafidz Sanjaya (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2025)
Twins Hotel Syariah Bandung is currently developing a digital-based service system to improve the efficiency and quality of services provided to guests. In the room reservation process, the hotel continues to face challenges such as manual data recording, errors in data management, and limitations in reporting. To address these issues, a team of lecturers from YPIB Majalengka of University initiated a training program on a digital hotel room reservation system designed to be simple yet capable of overcoming the classic limitations of manual processes. Furthermore, the need for ease of information delivery, service availability, and accessibility is crucial for the future development of the hotel's business. The activity was carried out in several stages, including system needs identification, system analysis and design, system development, preparation of training materials, implementation of the system in the hotel environment, and intensive training for relevant staff. The methods used include in-person and online training, hands-on practice with the system, and evaluation sessions to identify challenges during and after the training. The results showed an increase in staff skills in using the hotel room reservation application, a reduction in administrative errors, and improved time efficiency in serving guests. Additionally, the system is capable of generating automatic reports that assist management in decision-making. Overall, this community service activity had a positive impact and can serve as a model for the application of information technology-based community engagement that is practical and sustainable.